1995
DOI: 10.1037/0021-9010.80.6.697
|View full text |Cite
|
Sign up to set email alerts
|

Guilt appeals in advertising: What are their effects?

Robin Higie Coulter,
Mary Beth Pinto

Abstract: This study examined consumers' emotional responses, their attitudes toward advertisements and brands, attributions about the companies promoting the brands, and purchase intention for ads varying on level of guilt appeal. Sixty working mothers, a prime target of guilt appeals, participated in the study. Results indicated that moderate guilt appeals elicited more felt guilt in the working mothers than did low or high guilt appeals. Furthermore, emotional responses, particularly anger, mediated the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
247
1
16

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(277 citation statements)
references
References 37 publications
13
247
1
16
Order By: Relevance
“…Unfortunately, manipulating the appropriate level of guilt in an appeal has proven to be both crucial and difficult. Several studies have found that high levels of guilt may lead to reactance and counterarguing, thus discouraging the desired behavior (e.g., Coulter & Pinto, 1995). This is very similar to the reaction of consumers when presented with a high level of fear (Passyn & Sujan, 2006;Shehryar & Hunt, 2005).…”
Section: Literature Reviewmentioning
confidence: 78%
See 1 more Smart Citation
“…Unfortunately, manipulating the appropriate level of guilt in an appeal has proven to be both crucial and difficult. Several studies have found that high levels of guilt may lead to reactance and counterarguing, thus discouraging the desired behavior (e.g., Coulter & Pinto, 1995). This is very similar to the reaction of consumers when presented with a high level of fear (Passyn & Sujan, 2006;Shehryar & Hunt, 2005).…”
Section: Literature Reviewmentioning
confidence: 78%
“…Maladaptive responses include reactance and/or counterarguing (e.g., Coulter & Pinto, 1995). Reactance occurs when an individual feels s/he is being manipulated and the individual responds in some negative manner as a result (Brehm, 1966).…”
Section: Empathymentioning
confidence: 99%
“…Coulter and Pinto (1995) argued that comparable message manipulations may create different levels of guilt, depending on the context in which individual used to assess certain issue or visual object. …”
Section: The Justification Of Contro Versy From Petamentioning
confidence: 99%
“…The usage of the fear appeal in a certain advertising message will, however, be effective up to a certain point when its influence will begin to decline, since a large quantity of fear in an advertised message can lead to selective attention and contradict stated arguments by the observer (Belch and Belch, 2004). Guilt, which is connected with fear, is one of the emotional appeals that are often used and that was studied by Coulter and Pinto (1995).The authors relied on McGuire's theory (1969) that determined that both the low and the high guilt appeals inhibit the feeling of guilt, being that the former is due to a low level of attention while the latter is due to denying the messages that cause suspicion.…”
Section: Emotional Appeals In Advertisingmentioning
confidence: 99%
“…Reactions and attitudes of participants 4. Advertising video: "Aquafresh" Producer: Aquafresh Appeal: Humour Available at: https://www.youtube.com/watch?v=PcTTA6K5dMo…”
Section: Advertising Video: Short Descriptionmentioning
confidence: 99%